IoT Based Theft Detection Using Raspberry PI (International Journal of Food and Nutritional Sciences, 2021)
In the present day, Security and Safety are the major concern for the personage. We use C- Mount monitors in order to monitor and identify, but the C-mount has too much ability to record and needs staff to monitor the unlawful movement. Mobile device like Smart phones and I pad are used to perform daily tasks that are handle by commercial computers and laptop. Be overcome, we have found RP-3 model using IOT RP-3 model is much lowered compared to existing system with more appropriate settlement and less power use characteristics an “Internet Of Thing based Theft Detection using Raspberry Pi” Project where we had to use live video photo processing to espy stealer using motion as well as focus the area where motion reoccurred. In this model, we use a NRP-camera together RP-3 model together with a route with Virtual show infrared for night and Thumb drive for Data Storage. The model uses imaging to espy and emphasize the exact filed of movement in the camera when camera movement is espying.